WACANA RENCANA REKLAMASI TELUK BENOA DALAM FILM KALA BENOA - Suryadipta Wardhana, Anak Agung Ngurah Agung; Amanda Gelgel, Ni Made Ras; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2019)
ABSTRACT Watchdoc audio-visual production house aired a film titled "Kala Benoa". “Kala Benoa” showing various opinions of the people around Benoa Bay Bali if Benoa Bay will have reclaimed. The aim of this research is to find out the discourse which displayed by Watchdoc in the "Kala Benoa". This qualitative research is using discourseaanalysisxofxTeuncA.bvancccDijkcc method. The results of this research showed that Watchdoc takes role as the battleground for competing ideologies. “Kala Benoa” brings up several discourses i.e. Benoa Bay reclamation plan will damage the environment, Benoa Bay reclamation plan were indicated breaks the law, Benoa Bay reclamation plan will disrupts Balinese culture, Benoa Bay reclamation plan will eliminate the work of fishers, Benoa Bay reclamation plan will lead to a privatization, and an allegation of conspiracy in Benoa Bay reclamation plan. Keywords: Bali, Benoa Bay Reclamation Plan, Kala Benoa Film Discourse Analysis.